Risk and Resilience Factors for Psychobehavioral Symptom Trajectories Among Child Welfare–Involved Youth. Issue 9 (May 2021) - Yoon, Susan; Cage, Jamie; Pei, Fei; Barnhart, Sheila
The primary aim of the study was to investigate the development of psychobehavioral symptoms (internalizing, externalizing, and posttraumatic stress [PTS]) of child welfare–involved adolescents over a 3-year period and to identify predictors of the trajectories. Using three waves of data from the National Survey of Child and Adolescent Well-Being (NSCAW-II), latent growth curve modeling was conducted on a sample of 350 adolescents who were between 11 and 13 years of age at baseline. Findings indicated that adolescents' internalizing symptoms decreased over time, whereas externalizing symptoms remained stable over time. PTS symptoms decreased over time in girls, but not boys. Physical abuse predicted higher levels of externalizing behaviors and sexual abuse predicted a slower decrease in PTS symptoms. Greater child prosocial skills and higher quality of caregiver–child relationship were associated with lower initial levels of externalizing symptoms. In addition, a higher quality caregiver–child relationship and greater satisfaction with peer relationships were associated with lower initial levels of internalizing and PTS symptoms. Findings suggest that intervention strategies should consider gender, maltreatment type, and interpersonal and social skills to effectively prevent the development of psychobehavioral symptoms among child welfare–involved youth.